A modified multi-agent proximal policy optimization algorithm for multi-objective dynamic partial-re-entrant hybrid flow shop scheduling problem - Wu, Jiawei; Liu, Yong (Engineering applications of artificial intelligence, 2025)
This paper extends a novel model for modern flexible manufacturing systems: the multi-objective dynamic partial-re-entrant hybrid flow shop scheduling problem (MDPR-HFSP). The model considers partial-re-entrant processing, dynamic disturbance events, green manufacturing demand, and machine workload. Despite advancements in applying deep reinforcement learning to dynamic workshop scheduling, current methods face challenges in training scheduling policies for partial-re-entrant processing constraints and multiple manufacturing objectives. To solve the MDPR-HFSP, we propose a modified multi-agent proximal policy optimization (MMAPPO) algorithm, which employs a routing agent (RA) for machine assignment and a sequencing agent (SA) for job selection. Four machine assignment rules and four job selection rules are integrated to choose optimum actions for RA and SA at rescheduling points. In addition, reward signals are created by combining objective weight vectors with reward vectors, and training parameters under each weight vector are saved to flexibly optimize three objectives. Furthermore, we design an adaptive trust region clipping method to improve the constraint of the proximal policy optimization algorithm on the differences between new and old policies by introducing the Wasserstein distance. Moreover, we conduct comprehensive numerical experiments to compare the proposed MMAPPO algorithm with nine composite scheduling rules and the basic multi-agent proximal policy optimization algorithm. The results demonstrate that the proposed MMAPPO algorithm is more effective in solving the MDPR-HFSP and achieves superior convergence and diversity in solutions. Finally, a semiconductor wafer manufacturing case is resolved by the MMAPPO, and the scheduling solution meets the responsive requirement. •Consider partial-re-entrant flows, dynamic events, and multiple objectives in HFSP.•A novel multi-agent DRL scheme is developed for dynamic scheduling.•Adaptive trust region clipping is proposed to improve the constraint of policies.•Comprehensive experiments verify superiority in solutions quality and efficiency.